Income poverty and income support for minority and immigrant children in rich countries - Smeeding, Timothy M.; Robson, Karen; Wing, Coady; Gershuny, Jonathan I. (Luxembourg, 2009)
"The Luxembourg Income Study (LIS) and the databases underlying the European Statistics on Income and Living Conditions (EU-SILC) allow estimates of the extent to which immigrant and nonimmigrant children are poor across a wide range of rich nations. These data also allow estimates of the effects of social transfers that reduce poverty amongst all families with children. For all of the fourteen countries in the combined sample, children in migrant families have greater market-income poverty rates and greater disposable income poverty rates than do children in native-born families by a factor of about 2 to 1. Still, safety nets are important for all such families. For instance, before transfers, more than half of children in migrant families in France and Sweden are in poverty; however, after transfers, these rates are more than halved in these nations for both migrant and native-born children. In contrast, in the United States (US) the antipoverty effect of social transfers for both native and migrant families is negligible, because net transfers overall are insignificant in comparison with other rich countries.Thus the differences in benefits across countries, for both migrants and natives, are greater than are the differences within countries for these same groups. If the United States is to do better in fighting child poverty and realizing the economic and social potential of all of its children, it needs to expand its efforts on behalf of both immigrant and native children."